Current concepts in hand and upper extremity amputations. Issue 2 (March 2018) - Thayer, Mary Kate; Bellevue, Kate D.; Friedrich, Jeffrey B.
Abstract : Treatment of a hand or upper extremity amputation requires attention to anatomy, patient factors, cosmetic appearance, and potential functional outcomes of various treatment methods. This article provides a timely review of the most recent advances in the management and understanding of digit, hand, wrist and forearm level amputations with special attention to advances in the field in the past 2 yr.